Fibril‐Type Textile Electrodes Enabling Extremely High Areal Capacity through Pseudocapacitive Electroplating onto Chalcogenide Nanoparticle‐Encapsulated Fibrils. Issue 33 (25th September 2022) - Chang, Woojae; Nam, Donghyeon; Lee, Seokmin; Ko, Younji; Kwon, Cheong Hoon; Ko, Yongmin; Cho, Jinhan
Abstract: Effective incorporation of conductive and energy storage materials into 3D porous textiles plays a pivotal role in developing and designing high‐performance energy storage devices. Here, a fibril‐type textile pseudocapacitor electrode with outstanding capacity, good rate capability, and excellent mechanical stability through controlled interfacial interaction‐induced electroplating is reported. First, tetraoctylammonium bromide‐stabilized copper sulfide nanoparticles (TOABr‐CuS NPs) are uniformly assembled onto cotton textiles. This approach converts insulating textiles to conductive textiles preserving their intrinsically porous structure with an extremely large surface area. For the preparation of textile current collector with bulk metal‐like electrical conductivity, Ni is additionally electroplated onto the CuS NP‐assembled textiles (i.e., Ni‐EPT). Furthermore, a pseudocapacitive NiCo‐layered double hydroxide (LDH) layer is subsequently electroplated onto Ni‐EPT for the cathode. The formed NiCo‐LDH electroplated textiles (i.e., NiCo‐EPT) exhibit a high areal capacitance of 12.2 F cm −2 (at 10 mA cm −2 ), good rate performance, and excellent cycling stability. Particularly, the areal capacity of NiCo‐EPT can be further increased through their subsequent stacking. The 3‐stack NiCo‐EPT delivers an unprecedentedly high areal capacitance of 28.8 F cm −2 (at 30 mA cm −2 ), which outperforms those of textile‐based pseudocapacitor electrodes reported to date. Abstract : Herein, high‐performance pseudocapacitor textile electrodes prepared from chalcogenide nanoparticle assembly‐driven pseudocapacitive electroplating process are introduced. The research motivation is based on the possibility that the effective incorporation of conductive and energy storage materials into 3D porous textiles using favorable interfacial interactions plays a pivotal role in developing high‐performance energy storage devices.